Groundwater Quality Distribution in Development City between Surakarta-Kartasura (Ground Water Hidrologi System Contemplation in Bengawan Solo Recharge) - Alif Noor Anna (Universitas Muhammadiyah Surakarta, 2001)
This research is conducted in Kartasura-Surakarta s area especially from an area that relatively does not grow (recharge area) to an area growing to became a city (discharge area). The area is phisiographically restricted by a groundwater contour (i.e. 200 m from sea level) and by three rivers (i.e. Pepe, Wiro, and Bengawan Solo). This research has one objective to know the distribution of groundwater quality in Kartasura-Surakarta that is located between Pepe river and Wiro river. This research uses survey model and description comparative model completed by cheking the field. On the one hand, survey model measures physical data and density population data, and on the other hand, description comparative model is used to know the influence of physical factors and density population factors on groundwater quality. Physical data and density population data collected by using purposive proportional random sampling are analyzed with trend analysis model, statistical analysis model (i.e. parsiil correlation and one-way variant analysis). The result of this research shows that the groundwater quality in the field declines. The trend analysis proves that most of the parameter concentrations of groundwater quality increase from the recharge area to the discharge area. Furthermore, the conclusion is also supported by the result of parsiil correlation analysis that shows a positive correlation between the distance and the most of the parameters, although the positive correlation between the depth of groundwater and the parameters of groundwater quality is weak. Moreover, the results of one-way variant analysis to the selected factors (i.e. geology formation, density groundwater contour, and density population) with the parameters of water quality show that there is a strong difference on the most of the parameters.